Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0190864
|View full text |Cite
|
Sign up to set email alerts
|

Serine racemase deletion attenuates neurodegeneration and microvascular damage in diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is a leading cause of blindness. DR is recognized as a microvascular disease and inner retinal neurodegeneration. In the course of retinal neurodegeneration, N-methyl-D-aspartate receptor (NMDAR)-mediated excitotoxicity is involved. Full activation of NMDAR requires binding of agonist glutamate and coagonist glycine or D-serine. D-Serine is produced from L-serine by serine racemase (SRR) and contributes to retinal neurodegeneration in rodent models of DR. However, the involvement of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
1
18
1
Order By: Relevance
“…Supplementation with D-serine has proven to mitigate some of the symptoms of psychosis [37]. Patients with DR, by contrast, suffer from increased SRR activity and over production of D-serine, which elicits an excitotoxic effect on RGCs and ultimately contributes to cell death [40]. This will be addressed in more detail in the following sections.…”
Section: The Role Of D-serinementioning
confidence: 99%
See 2 more Smart Citations
“…Supplementation with D-serine has proven to mitigate some of the symptoms of psychosis [37]. Patients with DR, by contrast, suffer from increased SRR activity and over production of D-serine, which elicits an excitotoxic effect on RGCs and ultimately contributes to cell death [40]. This will be addressed in more detail in the following sections.…”
Section: The Role Of D-serinementioning
confidence: 99%
“…Studies have demonstrated a correlation between serine deficiency and systemic diabetes [77]. Inflammation potentially increases the expression and activity of SRR, and consequently increases the availability of D-serine for receptor binding [40]. The elevated levels of D-serine contribute to glutamate toxicity and induce RGC apoptosis [40].…”
Section: Diabetic Retinopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also reveal shortcomings in the classical retinal digest assay that has been cited as support for pericyte drop-out in diabetic conditions 20 , and they suggest that pericyte loss as a causative factor in diabetic vasculopathies needs to be reexamined, as it has already in the Akita mouse model 11 . Our analysis of immunostained retinas revealed that up to 50% of all pericyte somas were associated with a basement membrane bridge (combination of pericyte bridges and basement membrane bridged pericytes), which would have been miscounted as endothelial somas 47,48 in the retinal digest assay and potentially accounts for the approximately 30% 20 loss in pericyte density observed with this assay in diabetes and Ang2 stimulation. We…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, histological examination has produced inconsistent results with thicknesses that are unchanged (Ganapathy et al, 2009; Martin et al, 2004) or reduced (Ren et al, 2017) at 4-5 weeks after onset of diabetes. At longer periods of diabetes, retinal thinning (Li et al, 2010; Martin et al, 2004; Ozaki et al, 2018; Qian et al, 2018; Sachdeva et al, 2018; Yang et al, 2018; Zheng et al, 2007) or thickening (Berkowitz et al, 2009; Li et al, 2013) has been observed. Retinal thinning concurs with cell loss (Martin et al, 2004; Nishimura and Kuriyama, 1985) and not water loss (Berkowitz et al, 2012) in diverse rodent models of short-term diabetes (< 4 months).…”
Section: Discussionmentioning
confidence: 99%